2013
DOI: 10.1007/s10059-013-0266-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characterization of Arabidopsis GSK3-like Kinase AtSK12

Abstract: Plant GSK3-like kinases are key regulators that modulate a broad range of physiological processes such as cell growth, stomatal and flower development, responses for abiotic and biotic stress, and carbohydrate metabolism. Arabidopsis Shaggy/GSK3-like kinases (AtSK) consist of ten members that are classified into four subfamilies (I~IV). Only one of these Arabidopsis GSK3s, BIN2 (also named AtSK21), has been characterized by biochemical and genetic studies. BIN2 acts as a negative regulator in brassinosteroid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…AtSK12 regulates cell growth, but not stomatal development, whereas BIN2 regulates both these processes. It indicated that different AtSKs may have overlapping as well as specific functions [ 110 ].…”
Section: The Br Signalosome—an Updatementioning
confidence: 99%
“…AtSK12 regulates cell growth, but not stomatal development, whereas BIN2 regulates both these processes. It indicated that different AtSKs may have overlapping as well as specific functions [ 110 ].…”
Section: The Br Signalosome—an Updatementioning
confidence: 99%
“…BR also inhibits seedling photomorphogenesis and chloroplast development (Sun et al, 2010;Oh et al, 2012). In addition, BR negatively regulates leaf stomatal cell development through OST1 Activation by the Brassinosteroid-Regulated Kinase CDG1-LIKE1 in Stomatal Closure Tae-Woo Kim,a,1 Ji-Hyun Youn, b,1 Tae-Ki Park, a Eun-Ji Kim, a Chan-Ho Park, c Zhi-Yong Wang, c Seong-Ki Kim,b,2 and Tae-Wuk Kim a,d,2 BIN2, which inhibits a MAP kinase pathway involved in stomatal development (Gudesblat et al, 2012;Kim et al, 2012;Khan et al, 2013;Youn et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…After the separation of proteins by SDS-PAGE, the 32 P-labeled proteins were visualized by autoradiography. This assay was modified from previous research ( Kang et al, 2013 ; Youn et al, 2013 )…”
Section: Methodsmentioning
confidence: 99%